When to walk away : finding freedom from toxic people - Thomas, Gary (Gary Lee) (Zondervan, 2019)
"Whether it's a sibling, parent, coworker, or friend, we all know toxic people who seem determined to frustrate our life's calling. While you're seeking first God's kingdom, they're seeking to distract your focus and delay your work. Yet it's only once we learn to say no to bad patterns that we are set free to say yes to the good God has planned for us. Renowned writer and Bible teacher Gary Thomas uncovers surprising biblical principles for dealing with the toxic people in our lives. Drawing from years of serving as a pastor, Thomas shares real-life anecdotes, truths, and practical illustrations to set healthy boundaries and protect your life's calling. Each chapter includes insightful take-aways to begin applying right away. Discover how to: learn the difference between toxic people and 'difficult' people, find refuge in God when you feel under attack, discern when to walk away from a toxic situation, keep a tender heart even in unhealthy relationships, gain new vision and enthusiasm for seeking first the kingdom of God and investing in reliable people. We can't let others steal our joy or our mission. It's time to strengthen our defense, learn to set good boundaries, and focus on our God-given purpose."--Jacket.